Preparation of N-TiO2/SiO2 composites by solvothermal method and their photocatalytic properties - Chunli Wu; Xiaohao Dong; Lan Wang; Lei Zhang; Xiaotong Liu (Materials Research Express, 2022)
In order to improve the visible light catalytic activity of titanium dioxide (TiO _2 ) and ensure its long-term stability on the surface of concrete, an N-TiO _2 /SiO _2 composite was prepared using tetrabutyl titanate, nitric acid, and modified SiO _2 nanospheres as the precursors by a solvothermal method. The effect of nitric acid on the phase composition, morphology and photoelectric properties of the synthesized photocatalytic composites was systematically studied by various characterization methods. The results show that the optimum nitric acid/butyl titanate volume ratio is 1/6. The nitrogen-doped TiO _2 nanoparticles were uniformly dispersed on the surface of spherical SiO _2 with a diameter of 200 nm. The degradation rate of simulated pollutants (RhB) with pH 5 and 7 exceeded 95% within 30 min and the catalytic effect remained excellent after five repetitions without much weakening. The excellent visible photocatalytic performance can be attributed to the doping of N replacing part of the oxygen atoms in TiO _2 , forming the energy level of N 2p at the O 2p energy level and reducing the TiO _2 energy band gap to 2.99 eV. At the same time, the better dispersion of N-TiO _2 /SiO _2 prepared by this new synthesis method also plays an important role in the improvement of visible light photocatalytic activity.